A score for estimating survival in idiopathic pulmonary fibrosis with rest SpO2>88% - Soares, Maria Raquel; Pereira, Carlos; Ferreira, Rimarcs; Nei Aparecida Martins Coletta, Ester; Silva Lima, Mariana; Muller Storrer, Karin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Prediction models for survival at baseline evaluation have been proposed in IPF but some are difficult to use. The aim of present study was to develop a new mortality risk scoring system for patients with IPF at initial evaluation. Methods: One hundred twenty with definitive IPF were selected through a review of standardized medical records for interstitial lung diseases. Patients with resting SpO2